Meeting report of the 4th biennial Metabolism and Cancer symposium. (1st December 2021) - Abdel Hadi, Nadine; Boet, Emeline; Lahalle, Airelle; Lauture, Laura; Refeyton, Alice; Reyes‐Castellanos, Gabriela; Caplet, Nathalie; Carrier, Alice; Le Cam, Laurent; Mazure, Nathalie M.; Ricci, Jean‐Ehrland; Rocchi, Stéphane; et al.
Abstract : The 4th International meeting Metabolism and Cancer initially programed to take place in Bordeaux (France) was held virtually on May 27–29, 2021. The three‐day event was followed by around 600 participants daily from 47 countries around the world. The meeting hosted 21 speakers including selected talks and a keynote lecture from the Nobel Prize winner Sir Peter J. Ratcliffe (Oxford, UK). Presentations and discussions were divided in four scientific sessions: (a) Redox and energy metabolism (b) Redox and hypoxia (c) Metabolic profiling and epigenetic control and (d) Signalling, fuelling and metabolism in cancer and a general public session on cancer and nutrition. This report summarises the presentations and outcomes of the 4th annual Metabolism and Cancer symposium. We provide here a summary of the scientific highlights of this exciting meeting. Abstract : In May 2021, the 4th edition of the Metabolism and Cancer Symposium took place. This meeting hosted 21 speakers and a keynote lecture from the Nobel Prize winner Sir Peter J. Ratcliffe. Presentations were divided into four scientific sessions: (a) Redox and energy metabolism; (b) Redox and hypoxia; (c) Metabolic profiling and epigenetic control; and (d) Signalling, fuelling and metabolism in cancer and a general public session on cancer and nutrition.